Modelling the Piezoresistive Mems Cantilever for Chemical Sensing - Pannala Krishna Murthy, Vijay Prakash Singh, Rajesh Kanuganti, K. Durga Aparna (Mathematical Statistician and Engineering Applications, 2023)
MEMS (Micro Electro Mechanical Systems) sensors are used in acceleration, flow, pressure and force sensing applications on the micro and macro levels. Much research has focused on improving sensor precision, range, reliability, and ease of manufacture and operation. Over the last 15 years, researchers have explored the use of piezoresistive microcantilevers/ resonators as mass sensors because of their relative ease in fabrication, low production cost, and their ability to detect changes in mass or surface stress with fairly good sensitivity. However, existing microcantilever designs rely on irreversible chemical reactions for detection and researchers have been unable to optimize symmetric geometries for increased sensitivity. The cross-sensitivity of microcantilever sensors presents a major obstacle in the development of a commercially viable microcantilever biosensor for point of care testing. The presented paper aims to optimize the performance of piezoresistive cantilevers in cases where the output signal originates either from a static deflection of the cantilever. The presented optimizations for the static mode specifically targets the force sensitivity of piezoresistive cantilevers.